Managing people and technology: The challenges in CSR and energy efficient shipping. (December 2015) - Kitada, Momoko; Ölçer, Aykut
Abstract: This paper addresses the challenges of managers in the shipping industry to implement energy efficient measures in ship operations and their roles of managing both people and technology under the fulfilment of their corporate social responsibility (CSR). An increasing pressure on shipping companies to concern about marine environment, including energy efficiency, has led managers to consider CSR as their ethical business practices. It is an accepted norm that shipping is generally the most environmentally friendly mode of transport in terms of CO2 produced per ton nautical mile. Despite an extensive amount of research available to improve energy efficiency in shipping, the implementation of such measures has not been progressed by the industry as expected. This problem can be attributed to human element, which is connected to technology through designing and using it. In this context, it is problematic to understand that CSR is an inclusive set of corporate responsibilities in 'all-in-one' box. Hence, examining human element will help understanding the complexity of management in energy efficiency in shipping. The paper also identifies the limitations of CSR in business practices and the need of interdisciplinary research between people and technology in order to respond to managerial challenges in energy efficient shipping.